2019
DOI: 10.1016/j.foodhyd.2018.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Pickering stabilization of thymol through green emulsification using soluble fraction of almond gum – Whey protein isolate nano-complexes

Abstract: In this study, the soluble fraction of almond gum (SFAG) as a sustainable biopolymer source and whey protein isolate (WPI) were used for self-assembly preparation of SFAG-WPI nano-complexes through electrostatic interaction. The SFAG was characterized using 1 H and 13 C NMR. The influence of total biopolymer concentration (0.2-0.4 %w/v) and ratios (1:3-3:1) as well as of the pH (2-6) on the formation of complexes was established by visual, light scattering, surface charge, and spectrometric observations. The o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(22 citation statements)
references
References 43 publications
0
21
1
Order By: Relevance
“…A nano-particulate carrier of bioactive compounds targeting the colon has to survive the harsh acidic conditions of the stomach; otherwise, the distribution, release, and bioavailability of the compound can be uncontrolled (Jafari & McClements, 2017;Park, Saravanakumar, Kim, & Kwon, 2010). Natural polymers have been widely acknowledged to have many functions in foods, including as a stabilising agent (Manuhara, Praseptiangga, Muhammad, & Maimuni, 2016;Muhammad et al, 2019;Praseptiangga, Giovani, Manuhara, & Muhammad, 2017;Sedaghat Doost et al, 2019b). Xanthan gum, a non-toxic biopolymer produced by Xanthomonas campestris through fermentation, has been widely used as a thickening and stabilising agent in various products, including emulsion systems and micro particles.…”
Section: Introductionmentioning
confidence: 99%
“…A nano-particulate carrier of bioactive compounds targeting the colon has to survive the harsh acidic conditions of the stomach; otherwise, the distribution, release, and bioavailability of the compound can be uncontrolled (Jafari & McClements, 2017;Park, Saravanakumar, Kim, & Kwon, 2010). Natural polymers have been widely acknowledged to have many functions in foods, including as a stabilising agent (Manuhara, Praseptiangga, Muhammad, & Maimuni, 2016;Muhammad et al, 2019;Praseptiangga, Giovani, Manuhara, & Muhammad, 2017;Sedaghat Doost et al, 2019b). Xanthan gum, a non-toxic biopolymer produced by Xanthomonas campestris through fermentation, has been widely used as a thickening and stabilising agent in various products, including emulsion systems and micro particles.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, in another work, Jahed et al (2014) showed that this technique was capable to confirm the formation of complexes between the host and guest molecules; the complex ofcyclodextrin and curcumin was evaluated via NOE cross peaks (Figure 4 Recently, there has been a great demand for consumption of food products containing natural ingredients, including essential oils (EOs). The latter are hydrophobic volatile compounds that are increasingly attracting interest due to their antimicrobial and antioxidant properties (Sedaghat Doost et al, 2018b, Sedaghat Doost et al, 2019.…”
Section: Inclusion Complexesmentioning
confidence: 99%
“…In recent years, there is a growing demand from consumers for healthier and more convenient food products. With this in mind, edible polymers such as carbohydrates, lipids and proteins have been used in the food industry as emulsifiers, thickeners, food packaging and coatings, among others (Gutiérrez, 2018a;Sedaghat Doost et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Another option to modify the physicochemical properties of proteins is by self-assembly of protein structures with themselves or with others proteins, polysaccharides and active compounds (e.g. organic acids, flavonoids, phenolic compounds, among others), thus improving and creating novel structures with new functionalities which are not available by other means (Sedaghat Doost et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation